The study addressed as a teaching strategy the origin of life in high school (Research, Society and Development, 2020)
This work has the objective to discuss the hypotheses about the origin of life with an emphasis on classical experiments on spontaneous generation and biogenesis from a study  which renders the student protagonist in the process of teaching-learning about the theme. The study presents questions that are novel and the text was drawn from the textbook used by students. It was applied in a room on the 1st year of secondary education in a public school in Barra Mansa, during the Biology classes. With the application of  study, we noted that a more active attitude of students who showed interest in the construction of scientific knowledge about the proposed theme.